Islam and higher education : concepts, challenges and opportunities - Muborakshoeva, Marodsilton, 1967- (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2013)
"This book explores the different concepts of "a university" and the way they shape practice in Muslim contexts, with a particular focus on the Islamic republic of Pakistan. Higher education in Muslim contexts is often criticised for being incapable either of contributing to the socio-cultural and civilisational developments of society or of doing research and producing knowledge of a high standard. While the international organisations accuse universities of not helping the societies to become knowledge based and to compete at the global level, some Muslim scholars call for the creation of "authentic Islamic" educational structures that would, as they think, solve the problems of higher education. In addition, since 9/11 some have been accusing Islam and its institutions, especially madrasas of being terrorist establishments. Yet, these criticisms fail to consider the diverse historical evolutions of social institutions, including those of higher education, and the way political, ideological and economic contexts have an impact on them. These claims and generalisations are often made without sufficient evidence from the grass root level or conducting in-depth qualitative or historical research on the subject."--Publisher's description.
Higher learning in Muslim contexts : the past and present -- Modern developments of higher education in Muslim contexts -- Ideas of a university : key conceptual issues and challenges -- Concepts of a university in Pakistan -- The cases of universities visited -- Challenges universities in Pakistan face.
Includes bibliographical references (p. [156]-166) and index.
Keywords: Education, Higher -- Islamic countries; Education, Higher -- Pakistan; Islamic education; Islamic education -- Pakistan; Islamic universities and colleges; Islamic universities and colleges -- Pakistan